Determinants of Executive Compensation in Public Universities: An Exploratory Study of Australian Vice Chancellors - Evans, Robert; Preston, Alison; Evans, John (Research and Training Institute of East Aegean, Greece, 2012)
This study focuses on the pay determinants of Australian Vice Chancellors (VCs), in public owned universities using a specially constructed database over a 3 year time period. It aims to establish the degree of alignment between university outcomes and the pay of its VC. As with typical CEO pay studies it investigates size and profitability factors as predictors, however in line with the University mission it adds unique university measures of research and teaching excellence. The study finds pay to be linked to research output, low student to staff ratios and the proportion of student income derived from international students. In contrast to most private sector CEO pay studies, measures of size and profitability, although positively related to pay, are not significant.